Genetics and ecosystem effects of the invasive mussel Semimytilus algosus, on the West Coast of South Africa - Zeeman, Susanna Catharina Franzina (Department of Biological Sciences, 2016)
Invasive species can radically affect community composition and ecosystem processes, and human traffic has accelerated their spread. On the South African coast, 86 invasive species have been recorded, although until recently only the Mediterranean mussel Mytilus galloprovincialis and the barnacle Balanus glandula have had significant ecosystem effects on a large geographic scale. Semimytilus algosus was first detected at Elands Bay in 2009 and by 2010 it occupied 500 km of the West Coast of South Africa from Groenriviermond to Bloubergstrand. Given the fact that it is an ecosystem engineer forming dense beds, it is likely to have marked community effects. My study aimed to determine: (A) the identity, genetic composition and origin of the population, and (B) potential interactions between M. galloprovincialis and S. algosus and their effects on community composition. I conducted surveys to assess the abundance and zonation of S. algosus, analysed its competitive abilities by comparing its life-history strategies to other mussel species on the West Coast, and conducted field experiments to examine survival and interactions between S. algosus and M. galloprovincialis at different shore heights. I confirmed the identity of this species and found that the South African population has comparable genetic variation to the Chilean and Namibian populations. It spread to South Africa, seemingly through larval dispersal from Namibia, and now ranges from Groenriviermond in the north to Hout Bay in the south, spreading southward. It is most abundant on the low shore, with M. galloprovincialis on the mid shore. Mixed beds co-exist in the transition zone. Biodiversity in S. algosus beds is similar to that in M. galloprovincialis beds. High recruitment rates of S. algosus on the low shore, and its high genetic variation at all sites, enable it to colonise rock quickly and become established in new areas. The competitive ability of Semimytilus algosus is strongly related to shore height. It cannot survive on the high shore due to intolerance to desiccation. On the low shore its high recruitment rate offsets its high mortality due to wave action and predation.